Reviewing the difficulties of Hungarian higher education in the first quarter of the 20th century and the role of university youth after the ‘Great War’: A newsreel supported pragmatic survey - Kerepeszki, Róbert (Acta Neerlandica, 2021)
The basic idea of this paper was generated by some motion pictures shot on October events of 1918. This, at that time fundamentally novel media of mass communication can be considered as a visual interpretation of the moral behavior and the role attributed to the contemporary university youth in the series of revolutions after the ‘Great War’. Young people, many of them from universities, collected shocking experiences in the war that generated their moral and behavioral transition. At the time of the turn of the century there were development processes initiated in the Hungarian higher education, however, the war caused a break in these processes and, there were also certain structural changes introduced during and immediately after the end of the war which resulted in chaotic circumstances that kept on deepening the stress of students. Both the traditional press together with other printed documents and the contemporary newsreel have provided us with the sources being necessary and enough for making an attempt to answer, in what here follows, the questions: how the drastically changed, consequently chaotic situation within the Hungarian higher education along with the declined activity of student associations influenced the students, as well as how the most highlighted phenomena, such as the impact of war on everyday life and economy, the emergence and spread of violence, the reactions to the increased admission of female and Jewish students at universities affected the entire society and within this the university circumstances immediately after the armistice, and why the violence, radicalization, and “brutalization” of the so-called “war generation” became featuring at demonstrations.